Attributes influencing place attachment on public space: A review / Farid Al Hakeem Yuserrie ... [et al.] - Yuserrie, Farid Al Hakeem; Abdul Aziz, Azhan; Abdul Rahman, Norhafizah; Mohamed Saraf, Mohamad Haizam; Sayed Abul Khair, Sayed Muhammad Aiman (2022)
Place attachment in recent environmental-psychology based research has emerged as one important concept in the agenda to alleviate the risks of rapid urbanization in developing countries. Due to the broad name, definition and interpretation of the concept, the immensity and complexity of place attachment on public space literature are often difficult to navigate and wearisome. For that reason, this paper was set out to enquire into the existing literature on the place-based researches specifically for the attributes influencing place attachment on public space. Guided by a systematic review protocol, ninety four (94) documents were identified from the Scopus and Web of Science databases searches and only eighteen (18) related studies were methodically selected for analysis. Further review of the documents had resulted in three main themes of place attachment attributes on public space. They were Theme 1: physical attributes, Theme 2: activities attributes and Theme 3: image attributes. These themes provide further reflection on the place attachment archetype that could diversify the values of public places into a responsive environmental psychology.